Wastewater Treatment: From Cost Centre to Strategic Investment - Francesco Perri (European Scientific Journal, ESJ, 2026)
For a long time, urban wastewater treatment has been treated as a purely “defensive” sector: a cost centre necessary to comply with environmental standards and reduce the impact of discharges on rivers and seas. ​​However, in a historical phase marked by increasing water stress, extreme weather events and ecological transition, the scope of the problem is shifting: wastewater is no longer just waste to be managed, but a resource to be valued. ​​Therefore, this work aims to assess whether and to what extent purification can be reinterpreted as a strategic investment, capable of generating environmental, health and economic benefits. ​​The research is based on a qualitative methodology supported by quantitative evidence, based on European and national institutional documents, comparable series and indicators, as well as on case studies relating to water reuse, energy recovery and nutrient recovery. ​​The research questions concern: (RQ1) the overall economic return on investments; (RQ2) the contribution of purification to the circular economy; (RQ3) the costs of non-intervention, including sanctions, environmental damage and waste of resources. ​​The expected results indicate a positive social balance of investments, especially where purification enables reuse, energy autonomy and recovery chains. ​​The policy implications concern the need for multi-year planning, strengthening of governance and priority for the South, where the infrastructural deficit feeds a vicious circle of fines, environmental degradation and lower territorial attractiveness.